The Conversion of Agricultural Land in Urban Areas (Case Study of Pekalongan City, Central Java) - I Made Yoga Prasada; Masyhuri Masyhuri (Universitas Muhammadiyah Yogyakarta, 2019)
Agricultural land in urban areas has a strategic role as a provider of food for city resident, as well as supporting the environment of the urban area. The important role of the existence of agricultural land in urban areas over the past few decades faces a serious threat, namely the occurrence of agricultural land conversion. Therefore, this research was carried out with the aim to analyze the trend of agricultural land conversion in urban areas and to find out the factors that influence the agricultural land conversion in Pekalongan City. The data used in this study were secondary data sourced from the Central Statistics Agency of Pekalongan City. Data were analyzed using trend model analysis and tobit models. The results showed that the trend of agricultural land conversion in Pekalongan City was positive, so there was a tendency for the agricultural land conversion to increase from year to year. The factors that influence the area of agricultural land conversion in Pekalongan City were the real price of paddy at the farmer level and paddy productivity. Both of these factors have a negative sign, it shows that an increase in real prices of paddy and paddy productivity could reduce the agricultural land conversion in Pekalongan City.